2021
DOI: 10.1007/s00429-020-02200-9
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted morphological grey matter networks in early-stage Parkinson’s disease

Abstract: While previous structural-covariance studies have an advanced understanding of brain alterations in Parkinson's disease (PD), brain–behavior relationships have not been examined at the individual level. This study investigated the topological organization of grey matter (GM) networks, their relation to disease severity, and their potential imaging diagnostic value in PD. Fifty-four early-stage PD patients and 54 healthy controls (HC) underwent structural T1-weighted magnetic resonance imaging. GM networks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 92 publications
1
21
0
1
Order By: Relevance
“…Many studies indicated that the lateral parietal cortex (including SPL) plays an important role in PD with movement dysfunction (Tian et al, 2020), and the precuneus is located in SPL and involved in visuospatial processing, episodic memory, self-reflection, and consciousness (Guo et al, 2020). Abnormal spontaneous brain activities in right PCL (Chen B. et al, 2017;Guo et al, 2020;Sheng et al, 2021;Suo et al, 2021), left ITG (Jiang et al, 2016;Chen B. et al, 2017;Guo et al, 2020;Tian et al, 2020), and STG (Chen B. et al, 2017;Lin et al, 2017) in patients with PD had also been reported. Those are consistent with the previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated that the lateral parietal cortex (including SPL) plays an important role in PD with movement dysfunction (Tian et al, 2020), and the precuneus is located in SPL and involved in visuospatial processing, episodic memory, self-reflection, and consciousness (Guo et al, 2020). Abnormal spontaneous brain activities in right PCL (Chen B. et al, 2017;Guo et al, 2020;Sheng et al, 2021;Suo et al, 2021), left ITG (Jiang et al, 2016;Chen B. et al, 2017;Guo et al, 2020;Tian et al, 2020), and STG (Chen B. et al, 2017;Lin et al, 2017) in patients with PD had also been reported. Those are consistent with the previous results.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution (3.0 T or 7.0 T) MRI can provide information on pathologic changes in the brain of PD patients ( Sclocco et al, 2018 ). Previous brain network-related studies in PD patients have mainly focused on diagnosis; analyzing the relationship between GM network topology and the GM network determined from imaging data and disease severity can provide greater resolution for early diagnosis ( Suo et al, 2021b ). PD patients have higher E global and E local than normal subjects, which are unrelated to their clinical features ( Zhang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution divergence-based method has been used in morphologic brain network investigations including in PD ( Yoo et al, 2017 ; Fiorenzato et al, 2019 ; Yang et al, 2021 ). Specifically, Kullback–Leibler (KL) divergence ( Suo et al, 2021b ) was applied to construct the network according to the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐nine HC matched for age, gender, and years of education, with no history of neuropsychiatric disease, were recruited for comparative purposes. Details of inclusion and exclusion criteria are described in our previous paper (Suo et al, 2017; Suo et al, 2019; Suo et al, 2021a).…”
Section: Methodsmentioning
confidence: 99%